Ab Initio Prediction of Mechanical and Electronic Properties of Ultrahigh Temperature High‐Entropy Ceramics (Hf0.2Zr0.2Ta0.2M0.2Ti0.2)B2 (M = Nb, Mo, Cr). Issue 8 (7th May 2018) - Wang, Ya‐Ping; Gan, Guo‐Yong; Wang, Wei; Yang, Yan; Tang, Bi‐Yu
Abstract : High‐entropy metal diborides (Hf0.2 Zr0.2 Ta0.2 M0.2 Ti0.2 )B2 (M = Nb, Mo, Cr) are a new class of ultrahigh temperature ceramics. The novel structural, mechanical, and electronic properties of (Hf0.2 Zr0.2 Ta0.2 M0.2 Ti0.2 )B2 (M = Nb, Mo, Cr) are studied within density functional theory, with the compositional disorder being treated using the special quasi‐random structures technique. The elastic stiffness constants Cij, as well as bulk, shear and Young's modulus of (Hf0.2 Zr0.2 Ta0.2 M0.2 Ti0.2 )B2 (M = Nb, Mo, Cr) are studied to estimate the mechanical properties. The ductility is also investigated from several criterions, showing that (Hf0.2 Zr0.2 Ta0.2 M0.2 Ti0.2 )B2 (M = Nb, Mo, Cr) is still intrinsically brittle. The high Debye temperature of (Hf0.2 Zr0.2 Ta0.2 M0.2 Ti0.2 )B2 (M = Nb, Mo, Cr) indicates the strong interatomic interactions and good thermal conductivity. The detailed investigations of electronic structure reveal that covalent and metallic bonds are respectively formed in the boron layer and the metal layer, mixed ionic and covalent bonds are formed between the metals and boron interlayer. Abstract : The high‐entropy ceramics (Hf0.2 Zr0.2 Ta0.2 M0.2 Ti0.2 )B2 (M = Nb, Mo, Cr) are stable thermodynamically and mechanically. The elastic modulus follows the mixing rule. (Hf0.2 Zr0.2 Ta0.2 M0.2 Ti0.2 )B2 (M = Nb, Mo, Cr) possess higher Debye temperature. They exhibit a combination of metallic, covalent and ionic bonding. Mechanical properties of (Hf0.2 Zr0.2 Ta0.2 Nb0.2 Ti0.2 )B2 are more excellent than (Hf0.2 Zr0.2 Ta0.2 M0.2 Ti0.2 )B2 (M = Mo, Cr).